HUBUNGAN KADAR LEUKOSIT DAN TOTAL LIMFOSIT DENGAN KELAINAN PARU PADA PASIEN COVID-19 - Putra, Andika Fauzan; Khairani, Rita (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2024)
The impact of COVID-19 infection on the lungs is very broad. This lung organ disorder will affect the prognosis and also the patient’s quality of life. Markers are needed to identify the patient’s condition or patient’s prognosis so that they can estimate the patient’s condition from the start and determine further treatment and abnormalities that can be caused by the infection, especially in the patient’s lung organs. This study aims to reduce the incidence of post-COVID-19 pulmonary fibrosis by assessing the relationship between leukocyte levels and total lymphocyte count with lung abnormalities in COVID-19 patients. This research is an analytical study with a cross-sectional design using secondary data in the form of medical records from COVID-19 patients at the Budhi Asih Teaching Hospital, East Jakarta, with a total of 112 subjects. The data taken were leukocyte levels and total lymphocyte count based on laboratory results, and information on the patient’s pulmonary abnormalities documented in the medical record. The data were then analyzed by Chi-square test. The significance value used is p<0.05. Pneumonic lung abnormalities were dominated by increased leukocyte levels in 62 people (91.2%) and decreased total lymphocyte count in 63 people (94.1%). Leukocyte levels have a significant correlation with lung disorders (p = 0.021). The same thing was also shown by the total lymphocyte count which had a significant relationship with lung disorders (p = 0.001). There is a significant correlation between leukocyte levels and total lymphocyte count with lung abnormalities in COVID-19 patients.